Biomass accumulation, extraction and nutrient use efficiency by cover crops (Research, Society and Development, 2020)
The high biomass production of certain cover crops species is due to their high absorption capacity and nutrients use efficiency. Its potential for biomass production it is important to obtain productive plants using nutritional information especially in environments with low nutrient apport. The objective was to evaluate the biomass accumulation, extraction and nutrient use efficiency by cover crops growing in a soil of low fertility. The treatments were arranged in four randomized blocks, composed of seven cover crops: sunn hemp, spectabilis, pigeon pea forage, pigeon pea arbore, lab lab, jack bean and mucuna. To evaluate dry mass accumulation, crop growth rate and leaf area index, six plants were used in different times: 30, 45, 60, 75, 90 and 105 days after sowing. The cover crops differed in vegetative cycle, dry mass accumulation, yield, extraction and nutrient use efficiency, with better performance presented by pigeon pea arbore. The cover crops are good recyclers of nutrients, particularly nitrogen, potassium and calcium and have potential for use in the cultivation systems in the Northeast of Brazil.